Community Perception and Preference Towards the Rumbio Customary Forbidden Forest, Kampar Regency, Riau Province - Reza, Haris Aulia; Bahruni, Bahruni; Ichwandi, Iin (Jurnal Biologi Tropis, 2025)
The Rumbio customary forbidden forest is one of forests where local wisdom is applied by its indigenous people. This forbidden forest has high biodiversity, and the community greatly respects customary regulations. However, while some people strive to protect the environment, others neglect the forest, leading to a reduction in land that was once vast. This research aims to determine community perception and preference towards Rumbio Customary Forbidden Forest, Kampar Regency, Riau Province. This study employs interview methods, questionnaires, and document studies. The sample selection follows a proportional random sampling method, with qualitative and quantitative descriptive analysis techniques using a Likert Scale approach. The research results indicate that the community's perception of Rumbio customary forbidden forest reflects a complex relationship between ecological, social, and economic values. Strengthening community awareness of sustainable management and reinforcing the role of customary institutions in forest conservation is crucial.